Adjective Phrases - Matasović, Ranko (Array, 2002)
This paper represents a cross-linguistic study of adjective phrases (APs) in a sample of thirty languages. The syntactic behavior of APs is examined only in languages which have adjectives as a separate word class. It is argued that the class of adjectives which form APs can often be specified semantically and derivationally, and that such adjectives are usually non-prototypical, i. e., that they do not express the primary qualities of age, size, color, etc. It is also established that there is an asymmetry in the attributive and predicative use of APs. If, in some language, an AP can be used attributively, then it can also be used predicatively, but not vice versa. It is argued that attributive APs should be treated as relative clauses, and represented as such in the RRG framework.